Hydrofiber Dressing and Wound Repair: Review of the Literature and New Patents - G. Richetta, Antonio; Cantisani, Carmen; W. Li, Vincent; Mattozzi, Carlo; Melis, Luca; De Gado, Federico; Giancristoforo, Simona; Silvestri, Emidio; Calvieri, Stefano (Recent Patents on Inflammation & Allergy Drug Discovery, 2011)
Effective management of wound healing is a considerable challenge for clinicians. Patients underlying condition, accurate assessment of the wound and exudate, as well as selection of an appropriate dressing is all important factors for success. A variety of dressings are available to the clinician for the management of exudates. Hydrofiber dressings are a relatively new concept, and can be very cost effective because they can be worn for several days at a time. This report will review clinical evidences on the use of Hydrofiber dressing for the management of epithelial lesions, deal with current knowledge on the mechanism of action of this compound towards the epithelial wound healing process, immunological aspects and will also discuss relevant patents.
Keywords: hydrofiber